2010
DOI: 10.1016/j.nlm.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone acetate impairs memory and alters the GABAergic system in aged surgically menopausal rats

Abstract: In women, medroxyprogesterone acetate (MPA) is the most commonly used progestin component of HT. In vitro, MPA negatively impacts markers of neuronal health and exacerbates experimentally-induced neurotoxicity. There is in vitro evidence that these factors are driven by GABAergic and neurotrophic systems. Whether these effects translate to a negative impact on brain function has not been tested in vivo, clinically or preclinically. Here we evaluate the mnemonic and neurobiological effects of MPA in the surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
124
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(141 citation statements)
references
References 78 publications
(112 reference statements)
15
124
2
Order By: Relevance
“…MPA in combination with 17β-estradiol treatment impairs spatial reference memory relative to 17β-estradiol treatment alone or progesterone plus 17β-estradiol treatment in aged ovariectomized rats (107). In spatial working memory tasks, MPA-associated impairments were greater with higher levels of working memory load both in young and older ovariectomized adult rats (76,77). MPA administration may have long-term effects on spatial working memory beyond the time frame of administration, as MPA administered in either young adulthood, or middle age, impaired water radial-arm maze and Morris water maze performance when measured in middle age (76), with more pronounced effects seen with MPA administration in both young and middle adulthood.…”
Section: Progestinsmentioning
confidence: 96%
See 2 more Smart Citations
“…MPA in combination with 17β-estradiol treatment impairs spatial reference memory relative to 17β-estradiol treatment alone or progesterone plus 17β-estradiol treatment in aged ovariectomized rats (107). In spatial working memory tasks, MPA-associated impairments were greater with higher levels of working memory load both in young and older ovariectomized adult rats (76,77). MPA administration may have long-term effects on spatial working memory beyond the time frame of administration, as MPA administered in either young adulthood, or middle age, impaired water radial-arm maze and Morris water maze performance when measured in middle age (76), with more pronounced effects seen with MPA administration in both young and middle adulthood.…”
Section: Progestinsmentioning
confidence: 96%
“…Some studies [e.g., (384)] use retired breeders or oral administration of hormone, which is metabolized differently and poses challenges for dosage control. Further, natural versus synthetic progestins have different effects on cognition in rats depending on task type, with more negative outcomes associated with use of synthetic progestins such as medroxyprogesterone acetate (MPA) [e.g., (76,77,107,384)]. For example, tonic MPA impairs memory retention after a delay on the water radial arm maze, and exacerbates overnight forgetting on the spatial reference memory Morris water maze (77).…”
Section: Progestinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another in vitro study, it was demonstrated that medroxyprogesterone acetate and metabolites influenced memory, learning and other cognitive functions unfavorably through the GABA-ergic system, and could cause neuronal toxicity, this effect was not clearly revealed in in vivo clinical and preclinical studies [18].…”
Section: Discussionmentioning
confidence: 99%
“…MPA is a synthetic analogue of progesterone and acts like an agonist at progesterone receptors, but it also binds to androgen and glucocorticoid receptors, respectively [91,92]. A recent study found that MPA administered without estrogen impaired the performance of rats in the water radial arm maze and the spatial water maze tests [93].…”
Section: Type (Composition) Of Htmentioning
confidence: 99%